ISOLATION, CHARACTERIZATION AND ANTIBACTERIAL SREENING OF ANTIBIOTICS PRODUCED FROM STREPTOMYCES ISOLATED FROM DUMPSITE SOILS IN ILORIN, NORTH CENTRAL NIGERIA - Ahmed, Risikat Nike; Bamigboye, Mercy Oluwaseyi; Ajijolakewu, Kamoldeen Abiodun; Idris, Sheriffdeen Olakunle; Ajide Bamigboye, Nimat Toyosi (Malaysian Journal of Science, 2021)
Abstract Antibiotics are one of the most exploited metabolites produced by soil actinomycetes. This study isolated fifteen actinomycetes (A1 – A15) from dumpsite soils within Ilorin metropolis & screened them for antibacterial activity. Isolates were identified with morphology & biochemical characteristics.Their activity against clinical bacteria (Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae & Staphylococcus aureus) was determined. Their bioactive metabolites after fermentation was assayed for by agar well diffusion & compared with reference antibiotics. Molecular analysis of two most active isolates was done. The most active metabolite was subjected to GCMS. All isolates were identified as Streptomyces, 7 isolates exhibited activity against 3 test bacteria with highest (10.5mm±0.35) by Streptomyces griseoplanus while S. aureus demonstrated total resistance to all isolates. Secondary activity revealed 7 of the metabolites as effective against the bacteria with highest activity (28.5±1.04mm) by S. sparsogenes showing similar activity with Cefuroxime (28.01±0.01mm). The two most active isolates were Streptomyces griseoplanus strain NR725RL-ISP 5009 & Streptomyces sparsogenes strain NBRC 1308616S & RNA nucleotide similarity revealed close phylogenic relationship. GC-MS revealed10 compounds in S. sparsogenes strain NBRC 1308616S metabolite. Streptomyces from dumpsite soils within Ilorin produced bioactive compounds against clinical test bacteria and thus could be potential sources of antibiotics.